Limits of the separated-path Ramsey atom interferometer - Godun, R; Webb, C; Featonby, P; d'Arcy, M; Oberthaler, M; Summy, G; Foot, C; Burnett, K (IOP, 1999)
We describe in detail our caesium atom interferometer which uses a combination of microwaves and momentum-changing adiabatic transfer pulses. This combination allows us to achieve spatial separation between the arms of the interferometer. We account for the observed visibility of the resulting interference fringes and find that the effects which contribute the most are optical pumping and magnetic fields.